2020
DOI: 10.3947/ic.2020.52.4.503
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Causative Pathogens of Infective Arthritis and Risk Factors for Gram-Negative Bacterial Infections

Abstract: Background:The aim of this study was to describe the clinical and microbiological characteristics of infective arthritis and to analyze risk factors for Gram-negative bacterial infections that cause infective arthritis. Materials and Methods: Patients admitted between 2009 -2018 with infective arthritis in a single-tertiary hospital were evaluated retrospectively. Results: A total of 181 patients were enrolled in this study. Of them, 135 were native joint infection patients and 46 were prosthetic joint infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
13
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 17 publications
4
13
0
7
Order By: Relevance
“…In a study by Lee et al, methicillin-resistant S. aureus (MRSA) was identified as the causative agent in 39% of the total cases of S. aureus arthritis. The MRSA ratio was three times higher in healthcare-associated infections than in community-acquired infections [2]. This finding is similar to that reported by a previous domestic study in which MRSA was identified as the causative agent in 44% of the overall cases of S. aureus osteoarticular infections [3].…”
supporting
confidence: 89%
See 4 more Smart Citations
“…In a study by Lee et al, methicillin-resistant S. aureus (MRSA) was identified as the causative agent in 39% of the total cases of S. aureus arthritis. The MRSA ratio was three times higher in healthcare-associated infections than in community-acquired infections [2]. This finding is similar to that reported by a previous domestic study in which MRSA was identified as the causative agent in 44% of the overall cases of S. aureus osteoarticular infections [3].…”
supporting
confidence: 89%
“…MRSA has also been reported to be the causative agent in 38 -43% cases of native vertebral osteomyelitis in Korea [4,5]. Lee et al showed that a high MRSA ratio was associated with high resistance rates to ciprofloxacin (34.3%) and clindamycin (42.9%) in cases of S. aureus infection [2]. Although the clinical data on early conversion from intravenous to oral antibiotics for osteoarticular infections caused by methicillin-susceptible S. aureus are relatively abundant, the clinical data on early switch to oral antibiotics for MRSA osteoarticular infections are insufficient [6,7].…”
mentioning
confidence: 99%
See 3 more Smart Citations